Assessing Awareness of Forest Conservation Laws: Insights from a Community Study in Homabay County, Kenya - Shivachi, Taji Isindu; Atieno, Gabrilla Prisca; Nyamai, Daniel (African Journal of Education,Science and Technology (AJEST), 2024)
This study examines the awareness of forest conservation laws among communities in Homabay County, Kenya, and explores the sources of information on these laws. Data were collected through surveys, focus group discussions, and key informant interviews. Results reveal high levels of familiarity with certain prohibitions, such as unauthorized logging and timber trade, while awareness of other regulations, such as unauthorized burning and waste dumping, was comparatively lower. Social circles, including friends and relatives, emerged as the primary source of information, followed by announcements at funerals and social media. The study highlights the importance of community-based awareness campaigns and the need for targeted educational initiatives to improve understanding and compliance with forest conservation laws. Recommendations include enhancing formal education on environmental conservation, leveraging community during formal community gatherings (barazas) for information dissemination, and utilizing digital platforms for outreach. This research contributes valuable insights for policymakers, conservation organizations, and community stakeholders aiming to promote sustainable forest management and biodiversity conservation.